2015
DOI: 10.4314/ahs.v15i3.18
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial activity of some phenolic compounds from Cameroonians Allanblackia

Abstract: Background: Plasmodium falciparum, one of the causative agents of malaria, has high adaptability through mutation and is resistant to many types of anti-malarial drugs. This study presents an in vitro assessment of the antiplasmodial activity of some phenolic compounds isolated from plants of the genus Allanblackia. Methods: Tests were performed on well plates filled with a fixed parasitized erythrocytes volume. Compounds to be tested were then added in wells. After incubation, tritiated hypoxanthine is added … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…The 1 H NMR spectral data displayed a smaller J value of 7.6 Hz between protons H-2 and H-3 suggesting their monoaxial (cis) configuration and thus the absolute configuration in compound 4 could be (2R,3R) or (2S,3S). 22 Furthermore, Gaffield 21 reported that, in the CD spectrum The known compounds were identified as volkensiflavone (5) [24][25][26] , morelloflavone (6), 2,4,15,27 volkensiflavone-7-O--glucopyranoside (7), 17 morelloflavone-7-O--glucopyranoside (8), 2,17 (-)-catechin (9), 28 1,5-dihydroxyxanthone (10), 5,9 1,7-dihydroxyxanthone (11), 2,3,29 allanxanthone A (12), 5 6-deoxyisojacareubin (13), 3 hydrocotoin (14), 4 betulinic acid (15) 30 an inseparable mixture of -sitosterol and stigmasterol 31 and, an inseparable mixture of -sitosteryland stigmasteryl-3-O--glucopyranosides. 5 The absolute configurations of compounds 5-8 were determined as (2R,3S), (2R,3S), (2S,3R) and (2S,3R) respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The 1 H NMR spectral data displayed a smaller J value of 7.6 Hz between protons H-2 and H-3 suggesting their monoaxial (cis) configuration and thus the absolute configuration in compound 4 could be (2R,3R) or (2S,3S). 22 Furthermore, Gaffield 21 reported that, in the CD spectrum The known compounds were identified as volkensiflavone (5) [24][25][26] , morelloflavone (6), 2,4,15,27 volkensiflavone-7-O--glucopyranoside (7), 17 morelloflavone-7-O--glucopyranoside (8), 2,17 (-)-catechin (9), 28 1,5-dihydroxyxanthone (10), 5,9 1,7-dihydroxyxanthone (11), 2,3,29 allanxanthone A (12), 5 6-deoxyisojacareubin (13), 3 hydrocotoin (14), 4 betulinic acid (15) 30 an inseparable mixture of -sitosterol and stigmasterol 31 and, an inseparable mixture of -sitosteryland stigmasteryl-3-O--glucopyranosides. 5 The absolute configurations of compounds 5-8 were determined as (2R,3S), (2R,3S), (2S,3R) and (2S,3R) respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Phenolic compounds including flavonoid are one of the most important classes of antiplasmodial compounds [20]. The ethyl acetate fraction possess high phenolic and flavonoid content (254.8 ± 2.9 mg CAE/g dry fraction and 122 ± 0.77 mg CE/g dry fraction, respectively) which may be responsible for its antiplasmodial activity.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these considerations, compounds 10 (IC 50 : 0.65 μM; SI: 77; KB3‐1 cells), 11 (IC 50 : 0.16 μM; SI: >900; KB3‐1 cells), and 12 (IC 50 : 0.21 μM ; >700; KB3‐1 cells; Konziase, ) can be considered as hit compounds against P. falciparum FCR‐3, the cycloguanil‐resistant strain. Antimalarial hit compounds against the chloroquine resistant strains included compounds 8 (IC 50 : 0.95 μg/ml; Azebaze et al, ); 34 (IC 50 : 2.94 μM; Ganesh et al, ); 62 (IC 50 : 1.7 μM); 63 (IC 50 : 2.1 μM; De Monbrison et al, ); and 77 (IC 50 : 0.08 μg/ml; SI: 375 MRC‐5 cells; Konziase, ). In cutaneous leishmaniasis, the hit compounds included compounds 30 (IC 50 : 4.3 μM; SI: 18.3, macrophage cells; Fonseca‐Silva et al, ); 34 (IC 50 : 0.7 μM; SI: 10, macrophage cells; Montrieux et al, ); 92 (IC 50 : 0.2 μM; SI: 22, J774.A1 cells; Rizk et al, ); 95 (IC 50 : 8.1 μM; SI: 24.6, macrophage cells); and 96 (IC 50 : 3.2 μM; SI: 39.6, macrophage cells; Lage et al, ).…”
Section: Critical Assessment and Discussionmentioning
confidence: 99%
“…From the database searches, 830 (“malaria and flavonoids”: 540; “Chagas disease and flavonoids”: 60; “leishmaniasis and flavonoids”: 124; “dengue and flavonoids”: 106) potentially relevant records were identified, from which 737 were excluded after screening the titles or abstracts. The full reports of 93 articles were acquired: 83 studies related to natural flavonoids (Adinehbeigi, Razi Jalali, Shahriari, & Bahrami, ; Allard et al, ; Anusuya & Gromiha, ; Anusuya & Gromiha, ; Assis et al, ; Azebaze et al, ; Beer et al, ; Cabanillas et al, ; Castro, Barrios, Chinchilla, & Guerrero, ; Cheema et al, ; Cornelio et al, ; Coulerie et al, ; Cunha‐Rodrigues et al, ; Da Rocha et al, ; Da Silva, Maquiaveli, & Magalhães, ; De Monbrison et al, ; De Sousa et al, ; De Sousa et al, ; Dos Reis, Manjolin, Maquiaveli, Santos‐Filho, & da Silva, ; Ezenyi et al, ; Fonseca‐Silva, Inacio, Canto‐Cavalheiro, & Almeida‐Amaral, ; Fonseca‐Silva, Inacio, Canto‐Cavalheiro, Menna‐Barreto, & Almeida‐Amaral, ; Frabasile et al, ; Freitas et al, ; Ganesh et al, ; Gontijo et al, ; Grael, Albuquerque, & Lopes, ; Grecco et al, ; Güida et al, ; Heh et al, ; Houël et al, ; Ichino et al, ; Ijaz, Ahmad, Ahmad, ul Haq, & Wang, ; Inacio, Gervazoni, Canto‐Cavalheiro, & Almeida‐Amaral, ; Ismail & Jusoh, ; Jasmeen et al, ; Jin et al, ; Kapingu et al, ; Kiat et al, ; Kimmel et al, ; Konziase, ; Kraft et al, ; Kraft et al, ; Lage et al, ; Lage et al, ; Lehane & Saliba, ; Leite et al, ; Lu et al, ; Manjolin, dos Reis, Maquiaveli, Santos‐Filho, & da Silva, ; Marín et al, ; Marín et al, ; Mittra et al, ; Moghaddam et al, ; Montenegro, Gonzalez, Ortega‐Barria, & Luis Cubi...…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation